HUBUNGAN PEMANFAATAN INTERNET SEBAGAI SUMBER BELAJAR DENGAN MINAT BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Simanjuntak, Masri Monika; Indrawati, Henny; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Education is very important in the lives of every individual. Education is closely related to learning activities. One of the factors that influence learning activities is the interest in learning. Therefore, students' learning interests must be increased through the use of appropriate learning media to become a learning resource. The learning medium is internet media. The purpose of this research is to know the relationship between the use of the internet as a learning resource and the interest in studying economics education students of Riau University. The data required in this study is primary data collected by questionnaire or questionnaire. The research population is all students of Economic Education class of 2017 and 2018 Riau University as many as 157 students. Samples were taken by 113 students with simple random techniques. The analysis used is descriptive analysis and correlation analysis. The results showed a positive and significant relationship between the use of the internet as a learning resource and the interest in learning. The amount of internet utilization relationship as a learning resource with learning interests 0.649 with a sig of 0.000 < 0.05. This means the high low utilization of the internet as a learning resource has an impact on learning interests. The higher the use of the internet as a learning resource, the higher the interest in learning students.Key Words: Internet Utilization, Learning Resources, Learning Interests.